Peningkatan Kualitas Hidup Penduduk Desa Tuwang Kecamatan Karanganyar Kabupaten Demak Dengan Mengintegrasikan Nilai-Nilai Pancasila - Purmono, Purwono Sidik; Nafi'ul Munawwarah, Fika; Prabandari, Dyah Ajeng; Putri, Anatasya Nadia (Universitas Negeri Semarang, 2025)
Improving the quality of life of Tuwang villagers can be achieved through the integration of Pancasila values in community empowerment programs, particularly in the area of environmental health. This article discusses a strategic approach to improving quality of life by incorporating Pancasila principles such as gotong-royong, social justice and shared responsibility. The provision of clean water, elderly gymnastics and posyandu include environmental health programs that cannot be separated from the attention of the government implemented to increase community awareness and ability to maintain the health of their environment. The results of this approach are expected to not only positively impact the physical health of the population, but also strengthen social cohesion and a sense of togetherness within the community. Thus, the integration of Pancasila values in community empowerment is expected to make a significant contribution in creating a more prosperous and sustainable life in Tuwang Village